1996
DOI: 10.1080/00927879608825818
|View full text |Cite
|
Sign up to set email alerts
|

On a class of presentations of matrix algebras

Abstract: Recognizing when a ring is a complete matrix ring is of significant importance in algebra. It is well-known folklore that a ring R is a complete n × n matrix ring, so R ∼ = M n (S) for some ring S, if and only if it contains a set of n × n matrix units {e ij } n i,j=1 . A more recent and less known result states that a ring R is a complete (m + n) × (m + n) matrix ring if and only if, R contains three elements, a, b, and f , satisfying the two relations af m + f n b = 1 and f m+n = 0.In many instances the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Since by Lemma 2.5 x is invertible, then so is b in L, and we then obtain from the above two equations that f (i + j − 1) = b j−1 and f (i + j) = 0. We therefore get that In [Agn96], it is shown that for A = k a field, R(k; i, j, 1, 1) always maps to some M N (k) and…”
Section: The Rest Of This Subsection Is Devoted To the Description Ofmentioning
confidence: 78%
See 3 more Smart Citations
“…Since by Lemma 2.5 x is invertible, then so is b in L, and we then obtain from the above two equations that f (i + j − 1) = b j−1 and f (i + j) = 0. We therefore get that In [Agn96], it is shown that for A = k a field, R(k; i, j, 1, 1) always maps to some M N (k) and…”
Section: The Rest Of This Subsection Is Devoted To the Description Ofmentioning
confidence: 78%
“…The purpose of this article is in part to extend the results in [Agn96] that partly answer the above Question 1.7. The article is organized as follows.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…It is therefore natural to ask what happens if the first relation in Theorem 1.2 is replaced by a i f m + f n a j = 1. The ring R is by Theorem 1.2 a complete (m + n) × (m + n) matrix ring, but it could be the trivial ring; in [1] it is shown that if a ring R contains elements a and b such that ab m + b n a = 1 and b m+n = 0 where m = n, then R is the trivial ring. This result together with Theorem 1.3 strongly suggest the study of the universal ring that contains two elements a and f that satisfy a i f m + f n a j = 1 and f m+n = 0.…”
mentioning
confidence: 99%